A composite microstructure flexible pressure sensor based on MXene and its preparation method
The MXene@MP and MXene@PF layers were prepared by magnetic induction method and salt template sacrificial method, and a composite microstructure flexible pressure sensor was built, which solved the problems of complexity and high cost of traditional processes, and achieved high-performance pressure sensing effect. In various application scenarios.
Patent Information
- Application Number
- CN202411431891.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The preparation process of existing microstructure flexible pressure sensors is complex and expensive, making it difficult to achieve large-scale production, which limits its wide application in the field of pressure sensing.
The MXene@MP layer with microneedle array structure and the MXene@PF layer with a porous foam structure were prepared by magnetic induction method and salt template sacrificial method, and a composite microstructure flexible pressure sensor was built, and the sensor performance was improved by assembling the sandwich structure.
Achieve high force resolution and test stability, with a wide linear range of 0-72 kPa, a sensitivity of 60.2 kPa-1, a low-voltage detection limit of 1.6 Pa and excellent cyclic stability, suitable for the capture and capture of various physical stimuli and analyze.
Smart Images

Figure CN118954426B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of pressure sensing and relates to a MXene-based composite microstructure flexible pressure sensor and a preparation method thereof. Background Art
[0002] Two-dimensional materials have attracted widespread attention in scientific research and technological applications due to their unique physical and chemical properties. In the field of flexible pressure sensor research, this type of material is regarded as a key material for the preparation of high-performance sensors due to its high specific surface area and excellent conductivity. However, although common two-dimensional materials such as graphene, black phosphorus and MoS2 have shown certain potential, their inherent defects limit their widespread application in the field of pressure sensing. For example, graphene is difficult to effectively composite with other materials due to its poor water solubility; black phosphorus has insufficient environmental stability and is easily degraded in the air, affecting the reliability of its performance; and the preparation of MoS2 usually relies on the CVD process, which is complicated and not suitable for large-scale production.
[0003] Compared with these materials, the emerging two-dimensional material MXene and its derivatives are considered to be ideal materials for the field of flexible electronics because of their rich adjustable functional groups on the surface, excellent water solubility and plasticity, and the ability to be flexibly combined with other materials to form multifunctional materials. MXene not only has high conductivity and excellent mechanical properties similar to graphene, but also its interlayer spacing can be regulated by external pressure, which provides a broad application space for the construction of pressure-responsive mechanical sensors. These characteristics have important advantages for the construction of high-performance flexible pressure sensors.
[0004] At present, the research on microstructured flexible pressure sensors has made significant progress, but there are still many challenges to achieve the design and practical application of high-performance sensors. Traditional microstructure preparation processes such as template method, photolithography and CVD method usually have problems such as complex process, high cost and difficulty in large-scale production. In order to meet the needs of large-scale production and practical application of flexible pressure sensors, it is urgent to develop a new sensing mechanism that breaks the performance improvement and chooses one or the other and a simpler and more efficient sensing layer microstructure preparation technology. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a composite microstructure flexible pressure sensor based on MXene and a preparation method thereof. By using magnetic induction method and salt template sacrificial method, a MXene@MP layer with a microneedle array structure and a MXene@PF layer with a porous foam structure are successfully prepared, thereby building a composite microstructure flexible pressure sensor that can accurately identify mechanical change information in different application scenarios.
[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0007] A method for preparing a composite microstructure flexible pressure sensor based on MXene, comprising the following steps:
[0008] (1) Preparation of MXene-loaded microneedle layer (MXene@MP)
[0009] First, a PDMS mixture containing a PDMS base liquid and a curing agent is spin-coated on a quartz sheet and heated to cure to obtain a PDMS substrate; then a PDMS / CIP mixture containing a PDMS base liquid, a curing agent and reduced iron powder (CIP) is spin-coated on the PDMS substrate, which is then placed on a magnet to form a microneedle array structure, heated to cure, and a microneedle layer (MP layer) is formed on the PDMS substrate; then the PDMS substrate is immersed in n-hexane to separate the microneedle layer from the quartz sheet, and oxygen plasma treatment is performed to improve the surface hydrophilicity; finally, a MXene aqueous solution is evenly drop-coated on the microneedle layer to obtain a MXene@MP layer;
[0010] (2) Preparation of MXene-loaded foam layer (MXene@PF)
[0011] First, sodium chloride crystals are added to the PDMS mixture containing PDMS base liquid and curing agent, and the mixture is thoroughly mixed to obtain a PDMS / NaCl mixture; the PDMS / NaCl mixture is then spread flat in a culture dish and pressed into a thin film, which is heated and cured to obtain a PDMS / NaCl layer; the PDMS / NaCl layer is then placed in ultrapure water to completely dissolve the NaCl to form a porous structure, and a porous foam layer (PF layer) is obtained after peeling; finally, the porous foam layer is treated with oxygen plasma to improve the surface hydrophilicity and then immersed in a MXene aqueous solution to obtain a MXene@PF layer;
[0012] (3) Sensor assembly
[0013] The composite microstructure flexible pressure sensor adopts a sandwich structure. The bottom layer is a commercial PET substrate interdigitated gold electrode, the middle layer is a porous elastic foam skeleton MXene@PF layer coated with MXene, and the upper layer is a MXene@MP layer with a microneedle array structure. The microneedle side of the MXene@MP layer is attached to the MXene@PF layer.
[0014] Preferably, in step (1), the mass ratio of the PDMS base liquid to the curing agent in the PDMS mixture is 45:1.
[0015] Preferably, in step (1), the mass ratio of the PDMS base liquid, the curing agent and the reduced iron powder in the PDMS / CIP mixture is 5:1:3.
[0016] Preferably, in step (1), the conditions for oxygen plasma treatment are: power of 150 W and time of 1 min.
[0017] Preferably, in step (1), the concentration of the MXene aqueous solution is 10 mg / mL, and the drop coating is repeated until the MXene concentration in the MXene@MP layer reaches 1 mg / cm 2 .
[0018] Preferably, in step (2), the mass ratio of the PDMS base liquid to the curing agent in the PDMS mixture is 20:1.
[0019] Preferably, in step (2), the mass ratio of the PDMS mixture to the sodium chloride crystals is 1:4.
[0020] Preferably, in step (2), the conditions for oxygen plasma treatment are: power of 150 W and time of 1 min.
[0021] Preferably, in step (2), the concentration of the MXene aqueous solution is 4 mg / mL, and the immersion is repeated 3 times.
[0022] The present invention also provides a composite microstructure flexible pressure sensor prepared by the above preparation method.
[0023] The beneficial effects of the present invention are:
[0024] (1) The present invention uses magnetic induction method and salt template sacrificial method to successfully prepare MXene@MP layer with microneedle array structure and MXene@PF layer with porous foam structure, thereby building a composite microstructure flexible pressure sensor that can accurately identify mechanical change information in different application scenarios. At the same time, with ultra-high force resolution and test stability, the complete recording of the signal is achieved, providing information for analyzing and distinguishing human body movement patterns.
[0025] (2) The MXene-based composite microstructure flexible pressure sensor of the present invention exhibits good performance, including a wide linear range of 0-72 kPa and a maximum pressure of 60.2 kPa. -1 It has excellent sensitivity, fast response and recovery time, low pressure detection limit of 1.6 Pa and excellent cycle stability.
[0026] (3) The MXene-based composite microstructure flexible pressure sensor of the present invention can accurately capture a variety of physical stimuli ranging from slight wind changes to heavy object contact, demonstrating its potential for wide application in fields such as meteorological monitoring, communications, and military. Motion tests on different parts of the human body have found that, thanks to the high performance of the pressure sensor, it can provide more and more accurate body surface mechanical information. This provides strong technical support for new wearable health monitoring equipment such as physical therapy and motor learning. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a schematic diagram of the structure of the composite microstructure flexible pressure sensor prepared in Example 1.
[0028] Figure 2 This is a graph showing the effect of the number of immersion times on sensor performance in Example 2.
[0029] Figure 3 This is a graph showing the effect of MXene aqueous solution concentration on sensor performance in Example 3.
[0030] Figure 4 This is a graph showing the effect of the mass ratio of PDMS base liquid to curing agent in the PDMS mixture of the PF layer in Example 4 on the sensor performance.
[0031] Figure 5 This is a graph showing the effect of different microneedle hardnesses of the MP layer on sensor performance in Example 5.
[0032] Figure 6 These are SEM images of different mass ratios of the PDMS mixture and reduced iron powder in Example 6.
[0033] Figure 7 This is a graph showing the effect of the mass ratio of the PDMS mixture to the reduced iron powder on the sensor performance in Example 6.
[0034] Figure 8 The detection range and sensitivity (a), detection limit (b), response time and recovery time (c) of the composite microstructure flexible pressure sensor prepared in Example 1 are shown in the figure.
[0035] Fig. 9 The following are the test results of the actual application of the composite microstructure flexible pressure sensor prepared in Example 1, including (a) contact finger tapping sensing, (b) weight placement and removal, and (c) non-contact ear washing ball wind sensing.
[0036] Fig.10 The test results of the composite microstructure flexible pressure sensor prepared in Example 1 are as follows: (a) pulse recognition, the upper right sub-figure is the waveform of the pulse wave, (bc) voice recognition of words, and (df) recognition of daily throat movements.
[0037] Fig.11 The test results of the composite microstructure flexible pressure sensor prepared in Example 1 on the joint movement of the human hand include (a) flexion and extension of the second joint of the finger, (b) intermittent change of wrist bending angle test, and (c) continuous change of arm bending angle test.
[0038] Fig.12The test results of the composite microstructure flexible pressure sensor prepared in Example 1 on the human neck joint movement are as follows: (a) nodding, (b) tilting the head back, (c) left rotation, and (d) right rotation. DETAILED DESCRIPTION
[0039] For a clearer description, the present invention is further described below in conjunction with the embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0040] MXene can be purchased commercially or made in-house. In the present invention, MXene is made in-house, for example:
[0041] Preparation of MXene:
[0042] First, pour 30 mL of concentrated HCl solution into a polytetrafluoroethylene beaker, put it into a water bath and add a magnetic stirrer, and slowly add the weighed 1.875 g LiF powder into the polytetrafluoroethylene cup and stir for 10 minutes to form an etching solution. Then slowly add the weighed 0.8 g Ti3AlC2 powder into the polytetrafluoroethylene cup, adjust the stirring speed to ensure that the liquid does not splash, and finally stir for 24 h in a 40 ° C water bath to obtain a solution containing solid residue. After that, wash twice with deionized water, centrifuge at 4000 rpm / min for 3 min, pour the supernatant, and retain the precipitate. Subsequently, use the same centrifugation conditions and wash three times with 0.1 mol / L dilute hydrochloric acid to remove residual metal salts such as lithium fluoride on the product. Finally, wash continuously with deionized water until neutral, retain the precipitate to obtain multilayer titanium carbide Ti3C2T x . 35 mL of deionized water was added to the centrifuge tube containing the multilayer titanium carbide precipitate. Then, ultrasonic exfoliation was performed for 1 h under low temperature conditions. Next, centrifugation was performed at 3000 rpm / min for 30 min. After the centrifugation was completed, the supernatant was removed to obtain an aqueous dispersion of the few-layer MXene.
[0043] Example 1
[0044] Preparation of composite microstructure flexible pressure sensor:
[0045] (1) Preparation of MXene-loaded microneedle layer (MXene@MP)
[0046] The PDMS base liquid and curing agent were mixed in a mass ratio of 45:1 to obtain a PDMS mixture, and the PDMS mixture was placed in a vacuum oven for 30 min to remove bubbles. Next, a 5 × 5 cm 2Pour 2 g of the proportioned PDMS mixture on the quartz glass sheet and spin-coat at 900 rpm / min for 20 s to ensure uniform paving of the PDMS mixture. Then, place the quartz sheet with the PDMS mixture in an oven preheated to 100 °C for one hour to allow the PDMS to completely solidify and obtain a PDMS substrate;
[0047] Then, 2.5 g of a PDMS / CIP mixture containing PDMS base liquid, curing agent, and CIP (the mass ratio of PDMS base liquid, curing agent, and CIP was 5:1:3) was spin-coated on the PDMS substrate at a speed of 800 rpm / min for 20 s. Afterwards, the quartz slide was placed on a 5 × 5 cm 2 The uncured PDMS / CIP mixture will spontaneously aggregate under the action of magnetic force, gravity and surface tension to form a microneedle array structure. It is then placed in a 40°C oven for curing to form an MP layer on the PDMS substrate.
[0048] Then the PDMS substrate was immersed in n-hexane to separate the MP layer from the quartz sheet, and the MP layer was cut into 1 × 1 cm 2 The MP layer was treated with 150 W oxygen plasma for 1 min to improve its surface hydrophilicity. A 10 mg / mL MXene aqueous solution was evenly drop-coated on the MP layer and placed in a vacuum oven at 60 °C for 10 min for drying. The drop-coating and drying were repeated until the MXene concentration on the MP layer reached 1 mg / cm 2 , and finally the MXene@MP layer was obtained.
[0049] (2) Preparation of MXene-loaded foam layer (MXene@PF)
[0050] The PDMS base liquid and the curing agent were mixed in a mass ratio of 20:1 to obtain a PDMS mixture, and the PDMS mixture was placed in a vacuum box for 30 min to remove bubbles, and then sodium chloride crystals were added to the PDMS mixture (the mass ratio of the PDMS mixture and the sodium chloride crystals was 1:4), and the mixture was fully mixed to obtain a PDMS / NaCl mixture; 3.125 g of the PDMS / NaCl mixture was spread on a small culture dish and flattened with a hard plate to form a thin film, and then allowed to stand in an oven at 70 °C for 1-2 h to ensure that the PDMS / NaCl mixture was completely cured to obtain a PDMS / NaCl layer; the PDMS / NaCl layer was then placed in a beaker filled with ultrapure water and heated to 80 °C for 5 h to dissolve NaCl. After the NaCl was completely dissolved, the formed PF layer was peeled off from the culture dish with tweezers, and cut into 1 × 1 cm after drying. 2Then, the cut PF layer was treated with 150 W oxygen plasma for 1 min, completely immersed in 4 mg / mL MXene aqueous solution for 15 min to allow MXene to fully penetrate the porous structure of the PF layer, and then placed in a vacuum drying oven at 70 °C for 1 h. The immersion and drying steps were repeated three times to finally obtain the MXene@PF layer.
[0051] (3) Sensor assembly
[0052] The composite microstructure flexible pressure sensor adopts a sandwich structure. The bottom layer is a commercial PET substrate interdigitated gold electrode, the middle layer is a porous elastic foam skeleton MXene@PF layer coated with MXene, and the upper layer is a MXene@MP layer with a microneedle array structure. The microneedle side of the MXene@MP layer is attached to the MXene@PF layer. The structural diagram is shown in the figure. Figure 1 shown.
[0053] Example 2
[0054] The same as Example 1, the only difference is that the effect of the number of immersion times (immersion 1 to 6 times) in step (2) on the sensor performance is investigated. The results are as follows: Figure 2 As shown:
[0055] As the number of impregnations increases, the MXene loading capacity undergoes a process of first increasing, then stabilizing, and finally decreasing. Specifically, when the number of impregnations is between 1 and 3 times, the loading capacity increases significantly. Subsequently, when the number of impregnations continues to increase to 4 times, the growth rate of the loading capacity slows down, but there is still a slight increase. When the number of impregnations reaches 5 times, the loading capacity seems to have reached a plateau and remains at a relatively high level. However, when the number of impregnations further increases to 6, the loading capacity does not continue to increase, but begins to decrease. In general, this curve may indicate a saturation effect, that is, as the number of impregnations increases, the loading capacity no longer increases significantly after reaching a certain point, and may even decrease.
[0056] The sensitivity of the pressure sensor constructed by MXene@PF with different impregnation times can be compared by the slope of the curve. The observation results show that when the number of impregnations of MXene@PF is 3 times, the corresponding sensor shows the best sensitivity and linear response range. In contrast, when the number of impregnations reaches 5 times, even if the loading amount of MXene@PF is the largest, the performance of the corresponding sensor fails to reach the expected optimal performance.
[0057] Example 3
[0058] The same as Example 1, except that the effect of the concentration of the MXene aqueous solution in step (2) (the concentration of the MXene aqueous solution was 2, 4, 6, 8, 10 mg / mL) on the sensor performance was investigated. The results are shown in Figure 3 As shown:
[0059] When the mass concentration of MXene aqueous solution reaches 4 mg / mL, this pressure sensor exhibits the best sensing ability. Figure 3 The slope corresponds to the sensitivity of the sensor prepared with different MXene solution concentrations. For MXene solution, its concentration has a significant effect on the conductivity of the flexible conductive layer. When the concentration is only 2 mg / mL, due to the low content of active materials, the conductivity of the sensing layer will decrease, which in turn affects the sensitivity of the sensor. On the contrary, when the concentration of MXene solution is increased to 6 mg / mL or 8 mg / mL, although the content of active materials increases, the highly concentrated adsorbed and accumulated materials are easier to fall off when subjected to pressure and stretching, which will cause the conductivity to decrease during the recycling process and under greater pressure. This phenomenon is consistent with the experimental data results. Therefore, when the mass concentration of MXene solution reaches 4 mg / mL, the sensor exhibits better performance.
[0060] Example 4
[0061] The same as Example 1, except that the effect of the mass ratio of PDMS base liquid to curing agent in the PDMS mixture of the PF layer in step (2) (mass ratios of 5:1, 10:1, 20:1, and 30:1, respectively) on the sensor performance was investigated. The results are shown in FIG. Figure 4 As shown:
[0062] When the ratio of PDMS base liquid to curing agent increases from 5:1 to 20:1, the corresponding sensor performance gradually improves. When it reaches 30:1, that is, when the flexibility of the foam skeleton is the best, the sensitivity of the sensor decreases. The explanation for this experimental result is: when the initial ratio value is low, the sensor has poor deformation ability with changes in pressure load. As the mass proportion of the PDMS base liquid increases, the deformation ability of the foam skeleton becomes better, and the degree of deformation produced by the sensor is greater than the degree of deformation under the same pressure load at a low ratio value, thereby increasing the sensitivity of the sensor. However, when it is 30:1, the foam has poor mechanical strength and slow resilience that are difficult to withstand high pressure due to increased flexibility, resulting in a decrease in sensitivity.
[0063] Example 5
[0064] The same as Example 1, except that the mass ratio of the PDMS mixture of the MP layer to the reduced iron powder in step (1) was fixed at 2:1, and the effect of the mass ratio of the PDMS base liquid to the curing agent in the PDMS mixture (the mass ratios were 3:1, 5:1, and 7:1, respectively) on the sensor performance was investigated. The results are as follows: Figure 5 As shown:
[0065] The sensor corresponding to the MXene@MP layer with a moderate hardness of 5:1:3 has the best sensitivity. When the hardness of the microneedle is high, the high hardness limits the deformation of the microneedle, so that under the external pressure, the contact area between the microneedle and the MXene@PF layer changes less. This small deformation is difficult to effectively change the contact state between the microneedle and the foam, thereby affecting the range of resistance change, resulting in a decrease in the sensitivity of the sensor. When the hardness of the microneedle is low, even a small external pressure can cause significant deformation, which means that the microneedle is easily flattened and the contact area with the middle foam layer increases rapidly. Under the initial pressure, the large deformation of the microneedle does increase the contact area, resulting in an initial change in the electrical signal. However, as the pressure increases further, since the microneedle has been flattened, the increase in contact area becomes limited, causing the electrical signal change to saturate. This phenomenon can be confirmed by the sudden attenuation of the electrical signal at a pressure of 36 kPa on the 7:1:4 curve in the figure.
[0066] Example 6
[0067] The same as Example 1, except that the mass ratio of PDMS base liquid to curing agent in the PDMS mixture in step (1) was fixed at 5:1, and the effect of the mass ratio of PDMS mixture to reduced iron powder (mass ratios of 5:1, 5:3, 5:6, and 5:9, respectively) on the sensor performance was investigated. The results are as follows: Figure 6 and Figure 7 As shown:
[0068] Before comparing the performance, we first need to understand the effect of the change in CIP ratio on the microneedle morphology. Figure 6 , when the CIP ratio is low, the microneedles generated by the magnetic force appear to be relatively short and evenly distributed, with a moderate density. The morphology of these microneedles is relatively flat, and the tips are not particularly sharp. As the CIP ratio increases, the length and size of the microneedles increase, and the morphology begins to become irregular. The density also increases, and the spacing between the microneedles decreases, resulting in more contact between the microneedles. When the ratio reaches 5:1:6, the length of the microneedles increases further, and the morphology becomes more irregular and rough. The spacing between the microneedles further decreases, the density increases, and the microneedles appear to begin to overlap each other, which may indicate that the addition of CIP has a significant effect on the integrity of the microneedle structure. When the mass of CIP exceeds the entire PDMS mixture, at this stage, the length and irregularity of the microneedles reach a maximum, the microneedle structure becomes very rough, and the tip portion becomes wider and blunted. The overlap between the microneedles becomes more significant, indicating that the density reaches the highest level, which may lead to mechanical interlocking between the microneedles, thereby affecting the integrity of the material.
[0069] The actual performance comparison results are consistent with the predictions from SEM image observations. The sensor performance corresponding to the MXene@MP layer with a 5:1:3 ratio, which has the most uniform and complete microneedle array structure, is the best (e.g. Figure 7 ).
[0070] Key performance parameter test of flexible pressure sensor:
[0071] As a converter that converts pressure signals into electrical signals, flexible pressure sensors realize the digitization and visualization of pressure. In order to design flexible pressure sensors with excellent comprehensive performance and practicality, a series of performance parameters need to be quantitatively evaluated, including sensitivity (S), detection range, detection limit, response time, and recovery time. In this study, a test system consisting of a computer, a uniaxial force gauge, and a high-precision electrical signal detection source meter was used to study the sensor's sensing performance. Under the condition of setting the driving voltage to 1 mV, the test system measured the changes in the real-time output electrical signal of the sensor.
[0072] (1) Detection range and sensitivity
[0073] like Figure 8 a, it can be seen that the composite microstructure flexible pressure sensor has three linear sensing areas, when the pressure is in the range of 0-18 kPa, the sensitivity is 60.2 kPa -1 ; When the pressure is in the range of 18 - 58 kPa, the sensitivity is 12.8 kPa -1 ; When the pressure is in the range of 58 - 72 kPa, the sensitivity is 3.6 kPa -1 .
[0074] (2) Detection limit
[0075] like Figure 8 As shown in b, the sensor is able to detect tiny pressure changes as small as 1.6 Pa, which proves that the sensor has an ultra-low detection limit and high sensitivity, making it suitable for special applications.
[0076] (3) Response time and recovery time
[0077] In flexible sensor applications, short response and recovery times are essential to achieve fast, continuous, and accurate responses to external stimuli, which ensures high real-time and sensitivity of tactile sensing. For the skin-like pressure sensor in this work, its dynamic performance is as follows: Figure 8c. For instantaneous external pressure stimulation, the response time and recovery time of the sensor are 160 ms and 120 ms, respectively. The current signal of the sensor can respond quickly to external stimulation, and its response speed is faster than the normal reaction time of humans. This fast dynamic response characteristic makes the flexible pressure sensor have potential application value in the fields of tactile feedback and human-computer interaction.
[0078] Application testing:
[0079] (1) Plane practical application test
[0080] The sensor was placed on a flat tabletop and a series of practical tests were performed.
[0081] like Fig. 9 As shown in a, the sensor can accurately identify the Morse code signal of the finger tapping. In the continuous alternation of long and short signals, the current signal remains stable without signal drift, showing the potential of the device to be integrated with flexible fabrics as a lightweight signal communicator.
[0082] In addition, Fig. 9 In Figure b, a 20 g weight is placed on the sensor. When the weight is placed and removed, the output electrical signal shows obvious step changes and is very stable. In addition to being able to sense the contact pressure of the actual heavy object, the sensor can also sense the non-contact wind force caused by the wind, just like the skin feels the breeze. Fig. 9 As shown in Figure c, the current signal changes due to the wind blown by the ear-cleaning bulb, and the signal changes with the wind force, which once again proves the high sensitivity of the sensor. These actual tests show that the sensor can be used in meteorological monitoring, communications, military and other fields.
[0083] (2) Testing of micro human body pressure
[0084] The thin and skin-friendly pressure sensor is attached to the curved surface of the subject's wrist and fixed with flexible 3M-VHB tape to detect the pulse. The specific output signal is presented in Fig.10 In a, the blue waveform in the main figure represents the current change caused by the pulse over a period of time. It can be seen that the current waveform shows periodic fluctuations, which can fluctuate about 64 times in one minute, which is basically consistent with the rhythm of the heart's resting beating. And the shape is consistent with the shape characteristics of the human pulse wave in the sub-figure. The peak value of the current (P) corresponds to the systole period, when the blood pressure is the highest, and the trough (D) corresponds to the diastole period, when the blood pressure drops to the lowest. The small peak (T) behind the peak represents the reflected wave of the pulse wave, which is an important indicator of vascular elasticity and cardiac output characteristics. This set of data shows the potential application of flexible piezoresistive sensors in real-time monitoring of heart rate and pulse waveforms, which is of great significance for the development of wearable health monitoring devices.
[0085] In addition, flexible pressure sensors were attached to the subjects’ larynx to detect the tiny muscle movements caused by throat movements during vocalization. Fig.10 As shown in Figures bc, the current signal captured by the pressure sensor can accurately reflect the different words uttered by the subject. For example, the word "hello" is pronounced "nǐ hǎo" in Mandarin, and its unique three-tone tones show a clear inflection point in the current waveform. In contrast, the second word "world" is expressed in pinyin as "shì jiè", both of which have four-tone characteristics with falling tones, and the current signal waveform shows a continuous downward trend, showing the impact of different words on the current response pattern.
[0086] In addition to capturing voice characteristics, the flexible pressure sensor is also able to distinguish different laryngeal movements, showing high sensitivity to non-speech laryngeal movements. Fig.10 d shows the changes in the current signal during the swallowing action. Several obvious peaks can be observed, which correspond to the process of throat muscle contraction and relaxation, forming a unique current signal pattern. Fig.10 Figure e shows the current signal generated by coughing. Compared with swallowing, the peak of the cough signal is sharper and higher, which reflects the more rapid and strong contraction of the laryngeal muscles during coughing. This sharp change in signal pattern provides a reliable indicator for cough detection. Fig.10 f shows the waveform of the current signal when the subject hums softly. Compared with the previous two, the waveform produced by humming is wider and smoother, reflecting the continuous pressure changes caused by the vibration of the vocal cords.
[0087] Based on the above experimental results, it can be seen that the flexible pressure sensor can not only be used as part of the artificial vocal cord to capture speech, but also as a diagnostic tool to monitor and analyze various laryngeal activities, thus finding its application value in the fields of clinical medicine and speech therapy. This technological advancement indicates that real-time monitoring of subtle laryngeal movements in daily activities such as speaking, swallowing and coughing will become possible, which is of clinical significance for patients with speech or swallowing disorders.
[0088] (3) Testing of human joint movement
[0089] In preliminary experiments, the sensor was attached to the second joint of the index finger, and it was found that the sensor could work stably even when subjected to mechanical deformation such as bending and stretching, accurately capturing the signal changes generated by finger movement ( Fig.11 a). Repeated bending tests demonstrate the stability and repeatability of the sensor even under significant mechanical deformation.
[0090] Next, the researchers expanded their experiments to include sensors on larger joints, fixed to the back of the wrist and elbow. Fig.11 b shows a clear record of the sensor output current signal waveform when the wrist joint moves, showing its accurate reflection of the wrist movement process and amplitude changes. Fig.11 In Figure c, it can be observed that when the arm's movement angle is continuously changed, the current signal waveform shows a step-shaped upward trend related to the elbow joint movement, which further verifies the accuracy and reliability of the sensor in monitoring joint movement, especially in capturing dynamic and static pressure changes.
[0091] In further studies, sensors were attached to the back of the subjects' necks to monitor a range of neck movements. Fig.12 As shown in the figure, the sensor can accurately monitor and distinguish various movements of the neck. The excellent low-voltage detection capability and fit of the sensor enable it to sensitively capture the asymmetry of muscle movements on both sides of the human sagittal plane. This feature allows the direction of movement to be distinguished based on the current signal waveform. For example, in the neck rotation movement, although the left and right rotation movements are similar in pattern, Fig.10 The left-handed action waveform in c appears Fig.10 The different tailing peaks in the waveform of the right rotation movement in d provide a reliable indicator for distinguishing the direction of movement. This difference reflects the asymmetric pressure load generated by the neck muscles when performing different rotational movements, providing a new understanding of fine motor control based on muscle activity, and can further analyze data signals through machine learning to achieve accurate identification of different movements in the same part. This has great application value in the fields of human-computer interaction, physical therapy and motor learning.
Claims
1. A method for preparing a composite microstructure flexible pressure sensor based on MXene, characterized in that: The steps include: (1) Preparation of MXene-loaded microneedle layer First, a PDMS mixture containing a PDMS base liquid and a curing agent is spin-coated on a quartz sheet and heated to cure to obtain a PDMS substrate; then a PDMS / CIP mixture containing a PDMS base liquid, a curing agent and reduced iron powder is spin-coated on the PDMS substrate, and the PDMS substrate is placed on a magnet to form a microneedle array structure, heated to cure, and a microneedle layer is formed on the PDMS substrate; then the PDMS substrate is immersed in n-hexane to separate the microneedle layer from the quartz sheet, and oxygen plasma treatment is performed on the substrate to improve the surface hydrophilicity; finally, a MXene aqueous solution is evenly drop-coated on the microneedle layer to obtain a MXene@MP layer; (2) Preparation of MXene-loaded foam layer First, sodium chloride crystals are added to a PDMS mixture containing a PDMS base liquid and a curing agent, and the mixture is thoroughly mixed to obtain a PDMS / NaCl mixture; the PDMS / NaCl mixture is then spread flat in a culture dish and pressed into a thin film, which is heated and cured to obtain a PDMS / NaCl layer; the PDMS / NaCl layer is then placed in ultrapure water to completely dissolve the NaCl to form a porous structure, and a porous foam layer is obtained after peeling; finally, the porous foam layer is treated with oxygen plasma to improve the surface hydrophilicity and then immersed in a MXene aqueous solution to obtain a MXene@PF layer; (3) Sensor assembly The composite microstructure flexible pressure sensor adopts a sandwich structure, with the bottom layer being a PET-based interdigitated gold electrode, the middle layer being a porous elastic foam skeleton MXene@PF layer coated with MXene, and the upper layer being a MXene@MP layer with a microneedle array structure, and the microneedle side of the MXene@MP layer is attached to the MXene@PF layer.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the PDMS base liquid to the curing agent in the PDMS mixture is 45:
1.
3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the PDMS base liquid, the curing agent and the reduced iron powder in the PDMS / CIP mixture is 5:1:
3.
4. The preparation method according to claim 1, characterized in that: In step (1), the conditions for oxygen plasma treatment are: power of 150 W and time of 1 min.
5. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the MXene aqueous solution is 10 mg / mL, and the drop coating is repeated until the MXene concentration in the MXene@MP layer reaches 1 mg / cm 2 .
6. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the PDMS base liquid to the curing agent in the PDMS mixture is 20:
1.
7. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the PDMS mixture to the sodium chloride crystals is 1:
4.
8. The preparation method according to claim 1, characterized in that: In step (2), the conditions for oxygen plasma treatment are: power of 150 W and time of 1 min.
9. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the MXene aqueous solution was 4 mg / mL, and the immersion was repeated 3 times.
10. A composite microstructure flexible pressure sensor prepared according to the preparation method according to any one of claims 1 to 9.
